Analysis Of Stock Price In Retail Company That Applying E-Commerce In Idx - Salwis Salwis (Tasharruf: Journal Economics and Business of Islam, 2018)
Abstract            Retail companies have an important role in helping the economy of a country, but in the era of globalization like today every company must prepare a new strategy, especially retail companies because they see the current rapid technological developments. They must provide a product service system that is online-based (E-commerce) because the purchasing power or level of public consumption to retail companies decreases due to the provision of products in the online-based business is not inferior to retail companies. The purpose of the research is to find out the differences in the stock price of retail companies on the Indonesia Stock Exchange before and after implementing E-commerce. In this study using a quantitative approach with hypothesis testing using Paired Samples T-Test. The results showed that at PT. Matahari Department Store Tbk there are significant negative differences in stock prices before and after implementing E-commerce, PT. Sumber Alfaria Trijaya Tbk shows that there are no significant negative differences in stock prices before and after implementing E-commerce and PT. Mitra Adiperkasa Tbk shows that there are significant positive differences in stock prices before and after implementing E-commerce. Keywords : Stock Price, Retail Companies, E-Commerce.